Пневмоэлектромеханическая система управления расходом озоно-кислородной смеси в медицинском озонаторе - Кипенский, Андрей Владимирович; Куличенко, Вячеслав Викторович; Махонин, Николай Витальевич (НТУ "ХПИ", 2013)
In article the comparative analysis of systems of regulation and stabilization of flow rate of ozone-oxygen mixture in the medical ozone generators are given. The possibility of using the method of pulse width modulation of the system for implementing flow control is described. The experimental results of this system of management is stated. The substantial improvement of system weight and size, compared with other systems, are found.
Keywords: медицинская практика; озоно-кислородная смесь; озонотерапия; медикаментозные методы лечения; массогабаритные показатели; семейная медицина